PERSEPSI MAHASISWA UNIVERSITAS UDAYANA TERHADAP GAYA KOMUNIKASI MAUDY AYUNDA SEBAGAI JURU BICARA DALAM SIARAN PERS PRESIDENSI G20 - Devi, Putu Sinta Kharisma; Purnawan, Ni Luh Ramaswati; Gelgel, Ni Made Ras Amanda (E-Jurnal Medium, 2024)
The selection of public figures as an icon of public information delivery important role for the effectiveness of communication. This was also done by Indonesia Government by appointing Maudy Ayunda as Indonesia's spokesperson in the G20 Presidency. In order to ensure information conveyed properly, an approach using the right communication style is needed. This research was conducted to explain how Udayana University Students perceive Maudy Ayunda's communication style as a spokesperson in the G20 Presidency Press Release. The method used in this study is descriptive quantitative by using S-O-R (Stimus-Organism-Respons) Theory. The sampling technique used is non-probability which focuses on purposive sampling with data collection techniques using questionnaires. Based on the results of research on 130 respondents, the average score of respondents' answers was 4.26, which means that Udayana University students have a very positive perception of the communication style used by Maudy Ayunda in the G20 Presidency Press Release.